KEMAMPUAN BERBAHASA ANAK DENGAN MEDIA CERITA BERGAMBAR - Yatiningsih; Fu’ad Arif Noor (STPI Bina Insan Mulia Yogyakarta, 2020)
This research is to find out how to improve language skills using pictorial story media in BA 'Aisyiyah Gani Socokangsi Jatinom Klaten children. This research uses a type of classroom action research (PTK). The subjects of this study were children of group A BA 'Aisyiyah Gani Socokangsi Jatinom, Klaten, which consisted of 12 boys and 8 girls. The data collection techniques used were interviews, observation, and documentation. While the research instruments used were interview guidelines and observation sheets. The results of this study indicate that: 1) the use of pictorial story media is carried out in several steps, namely: a) preparing materials or learning materials to be delivered, b) conditioning students to be calm and paying attention, c) showing book covers while providing initial stimulation to the children then the teacher begins to read the story entitled